The ALMA survey to Resolve exoKuiper belt Substructures (ARKS) IX. Gas-driven origin for the continuum arc in the debris disc of HD 121617 - Perez-Marquez, S (EDP Sciences, 2026)
Context. Debris discs were long considered to be largely gas-free environments, where dynamical evolution is governed primarily by collisional fragmentation, gravitational stirring, and radiative forces. Recent detections of CO molecular line emission in debris discs demonstrate that gas is present, but its abundance and origin are still uncertain. The ALMA survey to Resolve exoKuiper belt Substructures (ARKS) observed both the gas and dust of several debris discs at high resolution and revealed a narrow ring of gas and dust in the disc HD 121617, with an asymmetric arc-like feature that is 40% brighter than the rest of the ring. Aims. An important open question is how representative the estimated CO masses are for the total gas mass in debris discs. We aim to constrain the total gas mass in HD 121617 using numerical models under the assumption that the dust arc is produced by hydrodynamical processes involving the gas. Methods. We used the hydrodynamical code Dusty FARGO-ADSG, in which dust is modelled as Lagrangian particles. We explored the effects of radiation pressure and dust feedback, as well as of varying the total gas mass on the dynamical evolution of the system. We compared these simulations with observations via radiative transfer calculations. Results. We find that an unstable gas ring can create a size-dependent radial and azimuthal dust trap. The total gas mass dictates the efficiency of particle trapping as a function of grain size. We find that two of our models, Mgas = 50 M and Mgas = 5 M, can simultaneously reproduce the observed arc in the ALMA band 7 continuum image and the radial outward offset of the VLT/SPHERE scattered light ring, driven by the combined effects of gas drag and radiation pressure. We further find a conservative lower limit of Mgas > 2.5 M and a conservative upper limit of Mgas < 250 M. Conclusions. If the ALMA band 7 asymmetry is caused by gas drag, reconciling the required gas mass with the observed 12CO emission suggests the presence of significant amounts of H2, consistent with the gas being primordial, that is, long-lived remnant material from the protoplanetary disc phase. In this scenario, HD 121617 would represent a hybrid disc, bridging the protoplanetary and debris disc stages. As an arc-shaped emission can alternatively be reproduced by a planet’s gravitational forcing, future observations are crucial to distinguish between these two scenarios. © The Authors 2026.